Деятельность и состояние художественного и этнографического отделов Центрального музея Тавриды накануне и в годы Второй мировой войны - Якубова, С.Д. (Культура народов Причерноморья, 2013)
В данной статье будет сделана попытка осветить деятельность и состояние
художественного и этнографического отделов Центрального музея Тавриды накануне и в годы Второй
мировой войны. На основе архивных материалов рассматриваются факты деятельности
вышеуказанных отделов Центрального музея Тавриды. Осуществляется попытка проанализировать
влияние и роль Второй мировой войны на существование отделов музея. У даній статті буде зроблена спроба висвітлити діяльність і стан мистецького та
етнографічного відділів Центрального музею Тавриди напередодні та в роки Другої світової війни. На
основі архівних матеріалів розглядаються факти діяльності вищевказаних відділів Центрального музею
Тавриди. Здійснюється спроба проаналізувати вплив і роль Другої світової війни на існування відділів
музею. This article will attempt to highlight the activities and the state of art and ethnographic department of
the Central Museum of Tauris before and during the Second World War. On the basis of archival materials are
considered the facts of the above departments of the Central Museum of Tauris. It attempts to analyze the impact
and role of the Second World War, the existence of sections of the museum.
During the Second World War, the Soviet government demanded the museum that they were working on. The
argument to this claim is the fact that the Soviet soldiers need moral support and need morale boost, namely the
ethnographic department contributed to this. Yet many of the exhibits had to be evacuated, but still this
evacuation did not bring positive results, because All exhibits have been irretrievably lost.
Further damage the ethnographic department of the German invaders inflicted, which destroyed many
ethnographic exhibits. It should not be surprising, because almost all of the exhibits are the ethnographic
department of household items. The German occupiers simply just went to the museum and the exhibits were
taken out of the show. None of the workers could not resist it.
The art department also suffered no small loss. If you compare this collection with the one that was in the World
Trade Center before the war and which has been destroyed, this collection represents much greater value.
Among these works were recognized masterpieces, famous masters. Save your work only the second or third
row. Although this does not detract from their value.